Medical students' perceptions of emergency medical care before and during the coronavirus disease 2019 pandemic. Issue 1 (6th April 2022) - Uejima, Toshifumi; Ota, Ikuo; Hamaguchi, Mitsuhide; Shigeoka, Hironori; Kurita, Takashi; Hiraide, Atsushi
Abstract : Aim: Understanding how medical students perceive emergency medical care is important in promoting education and recruitment in the field of emergency medicine. This study aimed to clarify the perceptions of undergraduate medical students on emergency medical care with a focus on comparing their perceptions before and during the coronavirus disease 2019 (COVID‐19) pandemic. Methods: Fourth‐year undergraduate medical students were invited to complete a self‐administered questionnaire in 2017 and 2020. Free comments on emergency medical care were analyzed via text mining. The relationships among categorical words were evaluated via correlation matrix and correspondence analysis. Results: The number of written words per student were not significantly different between 2017 (4.9 ± 3.4) and 2020 (5.3 ± 4.1). In 2017, the most frequently used word was "busy, " and the words "patients, " "life, " and "care" were not related to each other significantly. In 2020, the frequency of the word "busy" decreased and the word "patients" was related to "life" ( P < 0.01) and "care" ( P < 0.01). In the correspondence analysis, seven words including "life" and "care" were associated with "patients, " which demonstrates that these words tended to occur together. Conclusions: Although the responses of the medical students regarding emergency medical care before and during the COVID‐19 pandemic included similar words, their expressions tended to be related to patient care or patient life during the pandemic. This change in perception might cultivate a sense of mission and responsibility and an interest in emergency medical care among medical students. Abstract : This study aimed to clarify the perceptions of undergraduate medical students of emergency medical care focusing on the changes in perceptions before and during the COVID‐19 pandemic. We believe that our study makes a significant contribution to promote and to recruit students to emergency medicine.